2010
DOI: 10.1002/clc.20508
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Efficacy and Safety in Patients with Stage I‐II Hypertension

Abstract: Background: Nebivolol is a novel, β 1 -adrenergic receptor blocker with vasodilatory properties mediated through activation of the L-arginine/nitric oxide pathway. Hypothesis: This multicenter, double-blind, parallel-group, placebo-controlled study investigated the antihypertensive efficacy and safety of nebivolol in patients with stage I through stage II hypertension (sitting diastolic blood pressure [SiDBP] ≥95 mm Hg and ≤109 mm Hg). Methods: A total of 811 patients were randomized to placebo or nebivolol 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…The results of this study support findings from other nebivolol trials in hypertension [Greathouse, 2010;Neutel et al 2009;Saunders et al 2007;Weiss et al 2007;Van Nueten et al 1998, 1997: nebivolol is efficacious in reducing BP in participants with stage III hypertension, associated with an AE rate similar to that of placebo, and a low rate of AEs commonly associated with beta-blocker use (dyspnea, 0%; fatigue, 0%; sexual dysfunction, 0.7%) [Munzel and Gori, 2009]. The relatively low incidence of AEs in this study and other nebivolol clinical trials [Ambrosioni and Borghi, 2005] may be attributable to its high ß1-selectivity and NO-mediated vasodilatory effects [Munzel and Gori, 2009].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study support findings from other nebivolol trials in hypertension [Greathouse, 2010;Neutel et al 2009;Saunders et al 2007;Weiss et al 2007;Van Nueten et al 1998, 1997: nebivolol is efficacious in reducing BP in participants with stage III hypertension, associated with an AE rate similar to that of placebo, and a low rate of AEs commonly associated with beta-blocker use (dyspnea, 0%; fatigue, 0%; sexual dysfunction, 0.7%) [Munzel and Gori, 2009]. The relatively low incidence of AEs in this study and other nebivolol clinical trials [Ambrosioni and Borghi, 2005] may be attributable to its high ß1-selectivity and NO-mediated vasodilatory effects [Munzel and Gori, 2009].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the DBP and SBP reductions as well as the response rates observed in this trial are confirmatory of the BP reductions observed in the three registration trials of nebivolol monotherapy vs placebo conducted in over 2000 patients with stage I-II hypertension. 14,15,26 Use of antihypertensive therapies with complementary mechanisms of action is advocated for optimal control of BP due to the multifactorial aetiology of hypertension. 5 Perhaps for this reason, combination therapy of b-blockers with ACE inhibitors or ARBs has not always demonstrated additive benefits, as they both target the reninangiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…In the three trials that were pooled in our analysis [Greathouse, 2010;Saunders et al 2007;Weiss et al 2007], the observed rates of ED (0.5% of men) and OH (0.2%) were relatively low. (OH is a phenomenon that has been estimated to occur in 5-33% of the elderly and may be caused by various antihypertensive medications, including β-blockers [Verhaeverbeke and Mets, 1997].)…”
Section: Clinical Relevancementioning
confidence: 88%
“…All data reported in this publication were pooled from three similarly designed phase III, Greathouse, 2010]. Trials NEB-MD-202 and NEB-MD-302 were conducted in the US; trial NEB-MD-305 was conducted in the US, UK, Belgium, and the Netherlands.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation